Luda : a novel - Morrison, Grant (Del Rey, 2022)
"Luci LaBang is a star: for decades this drag artist has cast a spell over screen and stage. Now she's the leading lady in a smash hit musical. But as time takes its toll, Luci fears her star is beginning to dim. When Luci's co-star meets with a mysterious accident, a new ingenue shimmers onto the scene: Luda, whose fantastical beauty and sinister charm infatuate Luci immediately... and who bears a striking resemblance to herself at a much younger age. Luda asks Luci to share the secrets of her stardom, which is more than charisma. Because Luci is a master of the The Glamour, a mysterious magical discipline that draws on sex, drugs, and the occult for its trancelike effects. But as Luci tutors her young protegee in the art of magic, their fellow actors and crew members begin meeting with untimely ends. Now Luci wonders if Luda has mastered The Glamour all too well... and exploited it to achieve her dark ambitions. What follows is a descent into the demimonde of Gasglow, a fantastical city of dreams, and into the nightmarish heart of Luda herself: a femme fatale, a phenomenon, a monster, and perhaps, the greatest star of them all"--